Unveiling the tribological potential of MXenes-current understanding and future perspectives - Chhattal, Muhammad; Rosenkranz, Andreas; Zaki, Sana; Ren, Kexin; Ghaffar, Abdul; Gong, Zhenbin; Grützmacher, Philipp G. (Advances in colloid and interface science, 2023)
Reducing energy consumption and CO2 emissions by improving the tribological performance of mechanical systems relies on the development of new lubrication concepts. Two-dimensional (2D) materials have been the subject of extensive tribological research due to their unique physical and chemical properties. 2D transition metal carbides, nitrides, and carbonitrides (MXenes), with their tuneable chemistry and structure, are a relatively new addition to the family of 2D materials. MXenes' good strength and stiffness, easy-to-shear ability, capability to form wear-resistant tribofilms, and the possibility to control their surface chemistry make them appealing candidates to be explored for tribological purposes. This review provides a comprehensive overview of MXenes' tribology, covering their structure-property relationship, synthesis approaches, deposition methods to generate MXene coatings for tribological purposes, and their fundamental tribological mechanisms. Furthermore, detailed insights into studies exploring MXenes' tribological performance from the nano- to the macro-scale are presented with special emphasis on their use as self-lubricating solid lubricants, lubricant additives, and reinforcement phases in composites. [Display omitted] •Critical assessment of MXenes' structure, synthesis, coating deposition, and cross-scale tribology.•Discussion on MXenes' usage as solid lubricant coatings, additives, and fillers in composites.•Identification of MXene's cross-scale tribological potential and mechanisms to control friction and wear.•Existing bottlenecks of MXene tribology are identified, and future research is envisaged to guide tribologists.